The indexing of resources toward nazhir waqf - Lahuri, Setiawan bin; Sukmana, Raditya; Zuhroh, Ainun Amalia; Fatoni, Anwar (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This paper aims to find the factors for designing an index of the quality of developing human resources as nadzir waqf to control and to be the reference for waqf management in every waqf institution. Methodology – This study used a qualitative method with the Analytic Network Process. The data analysis shows the most dominant influence and determines the priority order, and decision-making. The data analysis will be the weighted sum for the performance ratings for each alternative across all attributes using the Simple Additive Weighting method and at the end, the Nazhir Wakaf Index (INW) value will be obtained. Findings – The research finds the factors in the internal and external resolutions bringing experts into the field by monitoring, and synergies with the government. The Nazhir Waqf Index that tried implemented is low with a score of 40.731. From the table and figure, it can be concluded that the highest variable design score of the Nazhir Wakaf Index (INW) at Pondok Modern Gontor is the assignment with a score of 100. With that assignment, the nadzir waqf has the autonomy to develop his competencies and abilities. Implications – If approached the index one would be the solution to the development. By offering a preliminary index and delivering informative advertising nadzir waqf resources will ensure the ability to provide efficient management. Originality – This research takes an important research gap to analyze the competence of nadzir waqf by making measurements in the development of nadzir waqf resources that can be used by any waqf institution.